A high-temperature heat pump for compressed heat energy storage applications: Design, modeling, and performance. (November 2022) - Hassan, Abdelrahman H.; Corberán, José M.; Ramirez, Miguel; Trebilcock-Kelly, Felipe; Payá, Jorge
Abstract: The current paper presents the design and performance of a high-temperature heat pump (HTHP) integrated in an innovative, sensible, and latent heat storage system. The HTHP has been designed to work between a heat source from 40 to 100 °C and a heat sink above 130 °C. An initial refrigerant analysis has revealed that R-1233zd(E) is the best candidate to meet the required performance and environmental considerations. The first part of this paper deals with the sizing and selection of the main components while discussing the challenges and working limits. A numerical model is also presented and validated. The second part of the paper is dedicated to develop parametric studies and performance maps under different operating conditions. The results show that the current HTHP, at a source temperature of 80 °C, consumes from 3.23 to 9.88 kW by varying the compressor's speed from 500 to 1500 rpm. Heat production is achieved in the form of latent heat (7.40 to 21.59 kW) and sensible heat (from 6.35 to 17.94 kW). The heating coefficient of performance ( C O P H T H P ) is around 4. Highlights: Design of a High Temperature Heat Pump with a heat sink above 130 °C. Comparison of different refrigerants and selection of R-1233zd(E). Model in IMST-ART including compressor correlations derived from manufacturer data. Analysis of source temperature, superheat, compressor losses and partial load. Heating coefficient of performance around 4 depending on operating conditions.